1976
DOI: 10.1128/aem.32.4.489-493.1976
|View full text |Cite
|
Sign up to set email alerts
|

Studies on glucose isomerase from a Streptomyces species

Abstract: Production and properties of glucose isomerase from a Co2+-sensitive Streptomyces species were studied. After 4 days of shaking cultivation at 30°C and 200 rpm, a maximum of 1.1 enzyme units per ml of broth was obtained. Cell-free glucose isomerase, obtained from mycelia heat-treated in the presence of0.5 mM Co2+, showed a 3.5-fold increase in specific activity over enzyme obtained from untreated mycelia. The optimum pH and temperature for the glucose isomerase were 7 to 8 and 80°C, respectively. The Michaelis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The pH optimum for activity of the enzyme was apparently lower than that of enzymes from other Streptomyces species (5,17,23,24,26). The glucose isomerases prepared from Actinoplanes missouriensis, B. coagulans, and Lactobacillus brevis also have a low pH optimum (6,21,31 (2).…”
Section: Fig 4 Sds-polyacrylamide Gel Electrophoresismentioning
confidence: 93%
See 2 more Smart Citations
“…The pH optimum for activity of the enzyme was apparently lower than that of enzymes from other Streptomyces species (5,17,23,24,26). The glucose isomerases prepared from Actinoplanes missouriensis, B. coagulans, and Lactobacillus brevis also have a low pH optimum (6,21,31 (2).…”
Section: Fig 4 Sds-polyacrylamide Gel Electrophoresismentioning
confidence: 93%
“…Most of the glucose isomerases (5,17,20,23,24,26) isolated to date showed an optimum temperature around 80°C. Hodge (13) indicated that degradation of ketoses occurs at high temperatures, characterized by a pronounced discoloration of an aqueous sugar solution.…”
Section: Fig 4 Sds-polyacrylamide Gel Electrophoresismentioning
confidence: 99%
See 1 more Smart Citation
“…These include Streptomycesphaeochromogenes (30), S. albus (19,24), S. bikiniensis (17), S. cinnamonensis (9), S. flavovirens (33), S. fradiae (14), and an unidentified Streptomyces sp. (3). Other organisms include Aerobacter cloacae (32), A. aerogenes (15), Lactobacillus brevis (34), Escherichia intermedia (16), Paracolobactrum aerogenoides (27), Bacillus megaterium (26), B. coagulans (35), and Actinoplanes missouriensis (20).…”
mentioning
confidence: 99%
“…Microbial enzymes are usually extracted by mechanical disruption (sonic oscillation, abrasive grinding, homogenization, or treatment with a French press) of the cell wall. The commonest method used in laboratories for the extraction of glucose isomerase is sonic disruption (2,7,10,11). Abrasive grinding is also employed for the enzyme extraction (6, 12).…”
mentioning
confidence: 99%